A regional solution for patient radiological dose management. (September 2016) - Garcia-Angosto, E.A.; Serna, A.; Garcia-Sanchez, A.J.; Garcia-Sanchez, F.; Ramos, D.
Abstract : Purpose: To highlight a novel methodology for patient dose management of radiological examinations in a regional public health framework. Material and methods: DoseWatch-GE is a multivendor and multimodality patient dose management software for radiological examinations. The framework in this study is a Region of Spain with 10 hospitals and 1.5 Million population. Dose indexes and examination protocols are recorded in individual patient files. Our methodology is divided into three foundations: (1) standardization of protocols, (2) Setting of Regional Diagnostic Reference Levels (RDRL), and (3) dose optimization. Results: Nowadays, 60 devices from 10 public hospitals are monitored: 13 CT's, 9 Interventional, 9 Mammo and 23 conventional. Every month the system is collecting approximately: 9000 CT, 800 Interventional, 2500 Mammo and 33000 conventional examinations. Standardization of protocols must be the first step because examinations nomenclature is highly variable among both manufactures and hospitals. We have established a master protocol list as reference for local protocols, thus allowing coherent data analysis. RDRL can be established and updated thanks to the massive amount of data available from a wide variety of equipment. This data might serve for future national DRL, currently not available. Dose optimization is supported by a multidisciplinary Dose Committee (radiologist, medical physicist, technologist, administration and application specialists), actively searching for dose reduction opportunities, based on comparative analysis with international DRL's and among similar equipments. Conclusion: We conclude that dose management systems might play an important role in the radiological patient safety task. Disclosure: None.